Silica Planar Lightwave Circuit Based Integrated 1 $×$ 4 Polarization Beam Splitter Module for Free-Space BB84 Quantum Key Distribution - Joong-Seon Choe; Heasin Ko; Byung-Seok Choi; Kap-Joong Kim; Chun Ju Youn (IEEE Photonics Journal, 2018)
We have developed an integrated polarization beam splitter (PBS) module with silica planar lightwave circuit technology for use in BB84 quantum key distribution (QKD). The PBS module is designed to operate on four linear polarizations of the horizontal/vertical/diagonal/antidiagonal direction, and shows the minimum polarization extinction ratio of 17.6 dB. When the module is loaded on the free-space BB84 QKD test-bed, quantum bit error rate and sifted key rate are 2.81% and 415 kb/s at clock rate of 100 MHz, respectively.